Harm reduction techniques among cisgender gay, bisexual, and queer men using anabolic androgenic steroids: a qualitative study - Eric Kutscher; Arslaan Arshed; Richard E. Greene; Mat Kladney (Harm Reduction Journal)
Abstract Background Anabolic androgenic steroids (AAS) are synthetic forms of testosterone frequently used as performance enhancing drugs among gay, bisexual, and queer (GBQ) men. Despite widespread use, associated harms, and the likely existence of an AAS use disorder, there is no medical consensus on standards of care for people who use AAS, with most medical providers focusing exclusively on abstinence. Individuals using AAS have developed community-based harm reduction strategies to mitigate these harms. Methods This paper is a sub-analysis of qualitative data obtained through semi-structured interviews with GBQ men using AAS for 8 or more weeks recruited through convenience and snowball sampling from clinical sites and LGBTQ + venues in New York City as well as through social media. Interviews were coded with themes developed using reflexive thematic analysis. Data related to harm reduction techniques were then re-analyzed through a prevention strategies framework lens of primary, secondary, and tertiary harm prevention. Results Thematic saturation was reached at twelve interviews in the primary analysis, with men reporting frequent use of multiple harm reduction techniques. For primary prevention, men avoided oral steroids and simultaneous substance use, tried to obtain AAS from reputable sources, used “cycling” to dose steroids, and practiced sterile injection techniques. Secondary prevention methods included patient-directed lab testing for hematocrit, liver and kidney function, cholesterol, prostate specific antigen, testosterone, and self-performed blood pressure checks. Tertiary prevention included donating blood and the use of medications without a prescription, including aromatase inhibitors, selective estrogen receptor blockers, aspirin, statins, angiotensin receptor blockers, clomiphene, and human chorionic gonadotropin. Conclusions Despite many GBQ men experiencing harms from anabolic androgenic steroids, community members have often sought harm reduction techniques in lieu of abstinence. Though many of these techniques embrace clinical reasoning and may be more broadly applicable, additional research is needed to understand the impact of each intervention on the overall health of individuals using AAS.